Allosteric modulators of metabotropic glutamate receptors: lessons learnt from mGlu1, mGlu2 and mGlu5 potentiators and antagonists. (26th October 2004) - Johnson, M.P.; Nisenbaum, E.S.; Large, T.H.; Emkey, R.; Baez, M.; Kingston, A.E.
Abstract : Although relatively few G-protein-coupled receptors are Class C, in recent years, this small family of receptors has become a focal point for the discovery of new and exciting allosteric modulators. The mGlu (metabotropic glutamate) receptors are illustrative in the discovery of both positive and/or negative allosteric modulators with unique pharmacological properties. For instance, allosteric modulators of the mGlu2 receptor act as potentiators of glutamate responses in clonal expression systems and in native tissue assays. These potentiators act to increase the affinity of orthosteric agonists for the mGlu2 receptor and shift potency curves for the agonist to the left. In electrophysiological experiments, the potentiators show a unique activation-state-dependent presynaptic inhibition of glutamate release and significantly enhance the receptor-mediated increase in G-protein binding, as seen with autoradiography. Similarly, potentiators of mGlu5 have been described, as well as allosteric antagonists or inverse agonists of mGlu1 and mGlu5. Binding and activity of the modulators have recently indicated that positive and negative allosteric sites can be, but are not necessarily, overlapping. Compared with orthosteric ligands, these modulators display a unique degree of subtype selectivity within the highly conserved mGlu family of receptors and can have very distinct pharmacological properties, such as neuronal frequency-dependent activity. This short review describes some of the unique features of these mGlu1, mGlu2 and mGlu5 allosteric modulators.